Ecosystem Carbon Stock of Mangroves at the Batticaloa Lagoon, Sri Lanka - K.A.R.S. Perera; M.D. Amarasinghe (The Open University of Sri Lanka, 2018)
Mangroves play an important role in sequestering organic carbon in tropical and subtropical coastal areas, accounting up to 15% of the total carbon deposited in coastal sediments. Sequestered organic carbon occurs both in standing plant biomass, as well as in the below ground root biomass and mangrove soils. Unavailability of quantitative data on carbon retention capacity of Sri Lankan mangrove ecosystems compelled the authors to carry out the present study with the objective of estimating the total ecosystem carbon content in mangrove eco systems in the Batticaloa lagoon, Sri Lanka. This is the largest lagoon situated on the east coast and the third largest brackish water system in the country. Data on vegetation structure were gathered according to the standard procedures and biomass of mangrove trees was determined by the Allometric method. Total Organic Carbon (TOC) in three depths, (0-15 cm, 16-30 cm and 31-45 cm) of mangrove soils was determined by dichromate-oxidation method followed by colorimetry. Total mangrove plant biomass was found to be 298 Mg ha-1, of which 246 Mg ha-1 was in the above ground components of the plants while 52 Mg ha-1 was in the below ground components. TOC embedded in biomass was calculated to be 158 Mg C ha-1out of which 131 Mg C ha-1was found to occur in above ground and 27 Mg C ha-1in below ground components. TOC in mangrove soils (up to 45 cm depth) was revealed to be 348 Mg C ha1. The total TOC of mangrove ecosystems in the Batticaloa lagoon was calculated to be 506 Mg C ha-1. Mangrove soils that sequester 68% of the organic carbon forms the largest fraction of the mangrove carbon sink. Below ground components account for only 5% of the total pool while the above ground biomass retains five times more (26%) carbon than the root biomass. These results assist pragmatic evaluation of ecological value of mangroves and justify their conservation and management.